Winter barley productivity in the southern part of the Rostov region when sowing sunflower as a forecrop with different seeding rates - A. A. Sukharev; G. V. Ovsyannikova; I. K. Kopman (Зерновое хозяйство России, 2024)
The current study was conducted in the southern part of the Rostov region in the agrotechnical crop rotation of the laboratory for cultivation technology of grain and row crops of the FSBSI Agricultural Research Center “Donskoy” in 2021–2023. The purpose of the study was to determine the eﬀect of seeding rates on productivity of various winter barley varieties sown after sunﬂower. The conducted study allowed identifying the response of winter barley varieties to diﬀerent seeding rates. The winter barley variety ‘Marusya’ on average over the years of research formed the mean maximum grain productivity of 6.43 t/ha when sowing with the lowest seeding rate (3 million pcs. of germ. grains per 1 ha). For the varieties ‘Vivat’ and ‘Foks 1’, the optimal seeding rate was 4 million pcs. of germ. seeds per 1 ha, and the obtained productivity was 6.31 and 5.81 t/ha, respectively. The response of the studied winter barley varieties to seeding rates was diﬀerent through the years, but the eﬀect of this factor was 4.6–10.5 %. Reliable diﬀerences in the experiment were obtained only for the variety ‘Vivat’ for all seeding rates. The winter barley productivity was determined by the choice of a variety, and the eﬀect of this factor ranged from 32.5 to 78.1 %. There was determined that when sowing with the lowest seeding rate (3 million pcs. of germ. grains per 1 ha), all winter barley varieties in the trial had the largest number of grains per ear and grain weight per ear with 36.3–43.2 g and 1.62–2.10 g, respectively. There was established that in the variant with this seeding rate, the varieties formed a heavy, large-size grain (nature weight of 637–660 g/l) with ‘1000-grain weight’ of 42.1–43.8 g and 10.8 to 11.3 % of protein in grain. There has been established an economic eﬃciency of cultivating the varieties ‘Vivat’, ‘Marusya’ and ‘Foks 1’ when sowing them with the lowest seeding rate of 3 million pcs. of germ. grains per 1 ha. With a low cost price of produced grain (5405–6136 rubles/t), in this variant of trial, the varieties obtained the maximum conditional net income (34378–45499 rubles/ha) and production proﬁtability (108–147%).